Integrating GWAS and eQTL to predict genes and pathways for non‐syndromic cleft lip with or without palate. (14th December 2020) - Yang, Jing; Yu, Xin; Zhu, Guirong; Wang, Ruimin; Lou, Shu; Zhu, Weihao; Fu, Chengyi; Liu, Jinsuo; Fan, Liwen; Li, Dandan; Shao, Qinghua; Ma, Lan; et al.
Abstract: Objective: To explore susceptibility genes and pathways for non‐syndromic cleft lip with or without cleft palate (NSCL/P). Materials and methods: Two genome‐wide association studies (GWAS) datasets, including 858 NSCL/P cases and 1, 248 controls, were integrated with expression quantitative trait loci (eQTL) dataset identified by Genotype‐Tissue Expression (GTEx) project in whole‐blood samples. The expression of the candidate genes in mouse orofacial development was inquired from FaceBase. Protein–protein interaction (PPI) network was visualized to identify protein functions. Go and KEGG pathway analyses were performed to explore the underlying risk pathways. Results: A total of 233 eQTL single‐nucleotide polymorphisms (SNPs) in 432 candidate genes were identified to be associated with the risk of NSCL/P. One hundred and eighty‐three susceptible genes were expressed in mouse orofacial development according to FaceBase. PPI network analysis highlighted that these genes involved in ubiquitin‐mediated proteolysis ( KCTD7, ASB1, UBOX5, ANAPC4 ) and DNA synthesis ( XRCC3, RFC3, KAT5, RHNO1 ) were associated with the risk of NSCL/P. GO and KEGG pathway analyses revealed that the fatty acid metabolism pathway ( ACADL, HSD17B12, ACSL5, PPT1, MCAT ) played an important role in the development of NSCL/P. Conclusions: Our results identified novel susceptibility genes and pathways associated with the development of NSCL/P.